Analysis of Clinical Characteristics and Severe Factors of 47 Cases of Psittacosis - Zhou Q; Cai C; Chen M (Infection and Drug Resistance, 2025)
Quan Zhou,1,2 Chunlin Cai,1 Minzhen Chen2 1Department of Hospital Infection Management, The Affiliated Changsha Hospital of Xiangya School of Medicine, Central South University, Changsha, Hunan, 410000, People’s Republic of China; 2Department of Infectious Diseases, The Affiliated Changsha Hospital of Xiangya School of Medicine, Central South University, Changsha, Hunan, 410000, People’s Republic of ChinaCorrespondence: Minzhen Chen, Department of Infectious Diseases, The Affiliated Changsha Hospital of Xiangya School of Medicine, Central South University, Changsha, Hunan, 410000, People’s Republic of China, Email 69422456@qq.comPurpose: Analyze the epidemiology, clinical manifestations, and imaging characteristics of 47 patients with psittacosis, combined with laboratory indicators, to explore influencing factors and early warning indicators of severe psittacosis.Patients and Methods: The analysis was conducted on case data of patients with psittacosis admitted to The Affiliated Changsha Hospital of Xiangya School of Medicine, Central South University, from January 2021 to September 2024, comparing differences between non-severe and severe patients, analyzing the correlation and impact degree between laboratory indicators and severity of the illness, finding independent influencing factors for the progression of psittacosis patients to severe.Results: The mean age of 47 patients was 61.53. 61.70% of patients were male. Most patients were retired and self-employed (23.40%). A clear history of exposure to poultry was observed in 36.17% of patients. These were mainly associated with hypertension (31.91%), cerebral infarction (10.64%), and Acquired Immune Deficiency Syndrome (10.64%). The median time from disease onset to hospitalization was 5 days. The median length of the hospital stay was 10 days. 85.11% of patients had fever. Chest CT features were mainly pulmonary lobe infectious lesions (93.62%). Compared with non-severe patients, severe patients had higher levels of aspartate aminotransferase, lactate dehydrogenase, D-dimer, C-reactive protein, and procalcitonin (P < 0.05). LDH, D-dimer, CRP, and PCT levels positively correlated with severe psittacosis (r > 0, P < 0.05). D-dimer level was an independent risk factor for the progression of psittacosis to severe disease (OR > 1, P < 0.05), with an AUC of 0.761. The optimal threshold was 2.50μg/mL, with 66.70% sensitivity and 78.80% specificity.Conclusion: Forty-seven patients with psittacosis were mainly elderly males, with fever as the typical symptom. Chest CT revealed infectious lesions in the lung lobes. D-dimer level could be an independent factor for the early warning of severe psittacosis.Keywords: psittacosis, d-dimer, severe illness, influencing factors, early warning